PENGARUH KEPEMIMPINAN, MOTIVASI, KEPUASAN KERJA, DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI SERTA DAMPAKNYA PADA KINERJA DINAS KOPERASI DAN USAHA KECIL MENENGAH ACEH - Saiful Bahri; Amri Amri; T. Roli Ilhamsyah Putra (Jurnal Magister Manajemen, 2018)
The achievement of the results of the planned programs must illustrate that the organization has achieved the target or in other words the organization's performance has meet expectations. Office of Cooperative and Small Medium Enterprises of Aceh in achieving its organizational performance desperately needs support from various inputs such as employee performance, that is the work result of quality and quantity achieved by an employee in carrying out tasks in accordance with the responsibilities given to him, in addition to leadership factors, work motivation, job satisfaction and organizational commitment contained within the organization. The analytical method used is Path Analysis. The result of analysis shows that there are direct effect of leadership variable, work motivation, job satisfaction and organizational commitment to employee performance and official performance, and employee performance to official performance, then there is indirect effect of employee performance in mediating leadership, work motivation, job satisfaction and organizational commitment to the performance of the Office of Cooperatives and Small Medium Enterprises of Aceh